Reframing the narrative: an analysis of print media reporting on Bihar floods - Priya, Ritu (Frontiers in Water, 2024)
In modern ways of ‘knowing water’, some narratives have gained greater acceptance than others. Mass media is a major component of the complex cultural process through which such narratives are created and sustained. This article elucidates vernacular print media as the site of construction of the dominant water meanings. Taking the case study of Hindustan, a popular Hindi newspaper from Bihar, India, this article analyses patterns of media reporting and the resulting discourse development on water management. Newspaper articles reporting on water issues were collected for the three monsoon months of July, August and September, 2019. The sample is taken for the monsoon season when floods and other water related events are expected to be more in news. 376 news items were found to report on water in which 7 major themes of reporting were identified. Second, discourse analysis was carried out on the 139 articles under the theme “monsoon floods”. These news items were analysed on five aspects- i) spatial outlook; ii) holistic approach; iii) fact-based reporting; iv) flood mitigation and v) gender-balanced reporting. Monsoon floods are the most frequently reported theme. Articles reported on damage due to floods as well as the measures of flood management. It was found that news items present a spatially disconnected and parochial pattern of reporting. News stories focused more on the short-term impacts of floods than on the policy problems that lie underneath. Fact based reporting is limited. News items on flood mitigation were favourable for structural interventions, particularly, embankments. The Gender lens is completely absent from the reports. Through this pattern of reporting, the news items create two narratives. The news items frame floods as unwelcome disasters that are exacerbated by rainfall in the catchment areas of upper riparian country Nepal as well as sluggish discharge from the Farakka Barrage. Secondly, news items also reported on interlinking of rivers and construction of embankments as favorable ways of flood control. This article problematizes these narratives and suggests a counter in terms of “living with floods”. Some suggestions for more nuanced and diversified reporting on the topic are discussed.